2021
DOI: 10.3390/v13081445
|View full text |Cite
|
Sign up to set email alerts
|

Live Bird Markets in Nigeria: A Potential Reservoir for H9N2 Avian Influenza Viruses

Abstract: Since 2006, multiple outbreaks of avian influenza (AI) have been reported in Nigeria involving different subtypes. Surveillance and molecular epidemiology have revealed the vital role of live bird markets (LBMs) in the dissemination of AI virus to commercial poultry farms. To better understand the ecology and epidemiology of AI in Nigeria, we performed whole-genome sequencing of nineteen H9N2 viruses recovered, from apparently healthy poultry species, during active surveillance conducted in nine LBMs across Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…The live animal market trade system plays a crucial role in the introduction of pathogens into new areas particularly long-distance disease spread (Martin et al, 2011;Zhou et al, 2015). Likewise, previous studies have described the important role of the live bird market in the epidemiology of avian influenza in Nigeria, but no report on the role of LPMs in the epidemiology of ASF in the country (Coker et al, 2014;Sulaiman et al, 2021). This study has demonstrated that ASFV is circulating in LPMs in Nigeria.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The live animal market trade system plays a crucial role in the introduction of pathogens into new areas particularly long-distance disease spread (Martin et al, 2011;Zhou et al, 2015). Likewise, previous studies have described the important role of the live bird market in the epidemiology of avian influenza in Nigeria, but no report on the role of LPMs in the epidemiology of ASF in the country (Coker et al, 2014;Sulaiman et al, 2021). This study has demonstrated that ASFV is circulating in LPMs in Nigeria.…”
Section: Discussionmentioning
confidence: 50%
“…However, these studies involved only one pig market with limited information on activities and pig movements in and out of the market. Studies in Nigeria have revealed that live bird markets play an important role in the ecology and epidemiology of Avian influenza in Nigeria (Coker et al, 2014;Fusaro et al, 2009;Sulaiman et al, 2021). Similarly, it has been reported that livestock farmers in Nigeria sell their animals through live animal markets to mitigate economic losses during disease outbreaks (Bolajoko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is therefore, a great threat to rural and commercial poultry production in Kaduna State. The implication of the spread and the carrier status of the rural household chickens could be of importance considering the fact that free ranged chickens were reported to constitute almost 50% of chicken population in Nigeria and are capable of scavenging around the environment spreading the NDV and other avian viral diseases to vaccinated and unvaccinated healthy exotic birds (FAO, 2018;Bitrus et al, 2020;Sulaiman et al, 2021). This study recorded an overall seroprevalence of 23% in the study area.…”
Section: Discussionmentioning
confidence: 69%
“…High levels of avian influenza viruses of public health concern (e.g. H5N1, H7N9, H9N2) have been detected in LBMs throughout Asia, the Middle East and Africa through longitudinal surveillance initiatives [8][9][10][11][12] . Indeed, many human cases of AIV infection have been associated with contact with poultry at LBMs 13,14 .…”
Section: Avian Influenza Ecologymentioning
confidence: 99%
“…Despite the current low number of human cases, influenza H5N1 circulation in poultry has continued unabated. Viral surveillance in LBMs has established that H5N1 circulation is occurring at levels similar to those detected during the peak period of human infections [8][9][10][11][12] . The current lack of human H5N1 cases may be linked to the dominant strain currently circulating (clade 2.3.2.1) being more 'avian-like' and not as readily able to jump the species gap to infect humans 25 .…”
Section: Current Influenza A/h5 Circulationmentioning
confidence: 99%